Untangling a New Breast Cancer Screening Technology. (IEEE spectrum)
An Australian firm plans to launch a competitor to X-ray mammography. The technique finds marks of breast cancer X-ray diffraction pattern of a woman's hair. The test on technology licensed from Veronica James, a physics professor at the Australian National University in Canberra, who reported in 1999 that she could detect an abnormality in the hair of women with breast cancer. In her research, James shot a concentrated beam of X-rays at single strands of hair. When the beam hit the hair, the diffracted X-rays formed a pattern on the detector related to the molecular structure of keratin, a protein found in hair. James claimed to find a diffuse additional ring in the diffraction pattern from hair samples of women with breast cancer.